A Five-Year Plan for the Development of the Central Provinces and Berar - Planning Commission (Planning Commission, 1947)
The ultimate object of all planning is the betterment of the lot of the people. This can be amplified by saying that all our people must be fed and all their primary needs fulfilled and they should be given employment—good, honest productive work—which will increase national wealth as also their own earning capacity. Simultaneously with this, Government will have to provide for a comprehensive organisation for social service which will look after the education, health, housing and social activities of the people including co-operation and local self-government.
Government of the Central Provinces and Berar